The international provision of pharmaceuticals: A comparison of two alternative theoretical strategies for global ethics - Ingo Pies; Stefan Hielscher (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2007)
Millions of people in the developing world lack access to curative drugs. Thomas Pogge identifies the cause for this problem in a lack of redistribution across borders. By contrast, this article shows that institutional shortcomings within developing countries are the main issue. The different outcomes are the result of diverging analytic approaches: (1) the philosophical approach to ethics versus (2) an economic approach to ethics. The article compares both approaches with regard to how they conceptualise and consecutively propose to solve the problem of providing life-saving pharmaceuticals to the poor in developing countries. A major common feature is that both approaches stress the importance of institutional design and incentives. However, there are important differences in detail: Pogge identifies the patent protection system as the crucial problem. He opposes compulsory licensing, which annuls patent protection on a case by case basis, as a pseudo-solution. Instead, he suggests separating pharmaceutical research from production. Research should be financed by the state and supplied as a public good to companies. In this way, drugs would be sold at market clearing marginal cost prices. Pogge argues for a large subsidy program financed by the rich which would lead to cheap drug prices that the poor can afford. By contrast, from the perspective of an economic ethics, the problem is not one of transfer but of governance: institutional deficits in developing countries hinder the poor from expressing their needs as actual demand on the market. From a theory point of view, the major difference between the two approaches lies in how they conceptualise normativity. In Pogge's approach, the role of ethics is to formulate reasons of duty in order to compel the rich to transfer resources to the poor. Here, normativity is understood as an obligation: the moral "ought" is meant to close gaps between the status quo and social imperatives. From the perspective of an economic approach, however, ethics is meant to help identify common interests. Normativity is understood as a heuristics: It seeks to identify and implement institutional arrangements for mutual benefit.
urn:nbn:de:gbv:3:2-4691
Keywords: A12; F02; H44; H51; H77; I11; I18; 330